2022
DOI: 10.1021/jacsau.2c00356
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Based Strategy for Predicting Protein Aggregation Propensity and Thermodynamic Stability

Abstract: Novel drug candidates are continuously being developed to combat the most life-threatening diseases; however, many promising protein therapeutics are dropped from the pipeline. During biological and industrial processes, protein therapeutics are exposed to various stresses such as fluctuations in temperature, solvent pH, and ionic strength. These can lead to enhanced protein aggregation propensity, one of the greatest challenges in drug development. Recently, ionic liquids (ILs), in particular, biocompatible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…Overall, formulations lacking IL showed less negative zeta potential values compared to the ionogel formulations. This indicated that the inclusion of IL served to reduce the aggregation propensity and induce a more negative surface charge in each system compared to formulations lacking IL, in line with previous work. ,, …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, formulations lacking IL showed less negative zeta potential values compared to the ionogel formulations. This indicated that the inclusion of IL served to reduce the aggregation propensity and induce a more negative surface charge in each system compared to formulations lacking IL, in line with previous work. ,, …”
Section: Resultssupporting
confidence: 89%
“…13 In the absence of IL, the D h and polydispersity index (PDI) values were relatively higher for each formulation indicating enhanced aggregation propensity, which can lead to reduced structural stability. 45,46 We found that [Cho][DHP] and [Cho][OAc]-ionogel formulations showed relatively more negative zeta potential values compared to the [Cho][Cl]-ionogel formulations (Figure 3A−D and Table S1). PVP inclusion also resulted in more negative zeta potential values.…”
Section: Phenobarbital Solubility In Ionogel Formulationsmentioning
confidence: 94%
“…The T m of IgG in the buffer is found to be 74 °C which is in corroboration with the literature. 14,15 However, an increment in the T m values can be seen in the presence of formulations F2, F4, F5, and F6 changing from 74 °C (buffer) to 75, 87, 83, and 75 °C respectively. The overall sequence of T m is F4 > F5 > F2 = F6 > control>F7 = F1 > F3.…”
Section: Thermodynamic Stability Studies Of Igg In the Presence Of Va...mentioning
confidence: 98%
“…ILs have shown great potential for use in medication delivery applications. However, choline-based ILs, in particular, have stood out as drug carriers owing to their biocompatible nature, accessibility, and cost-effective properties. , Mitragotri and group have illustrated the use of choline-based ILs and deep eutectic solvents (DESs) as an oral delivery platform for local as well as systemic delivery of therapeutic antibodies. Shmool et al have also recently investigated the IgG4’s propensity to aggregation in the presence of choline chloride [Ch]­Cl. Very recently, our research group investigated the stability profile of IgG in the presence of choline-based ILs and found that the protein’s conformational and colloidal stability improved significantly in the presence of choline acetate ([Ch]­[Ac]).…”
Section: Introductionmentioning
confidence: 99%
“…In sharp contrast, stabilization of proteins by artificial means is usually achieved by addition of large stoichiometric excess kosmotropic salts, 5 saccharides and related polyols, 6 polar amino acids, 7-10 polymers, 11-17 nanogels 18 and ionic liquids. [19][20][21] A common characteristic of these additives is that typically their high concentration (>100 mM for small molecules or 10 mg mL -1 for polymers) is required to achieve satisfactory results. In such cases, however, the high concentration of additives changes the general properties of the solution, including viscosity, ionic strength, refractive index and chemical compatibility.…”
mentioning
confidence: 99%